The Labyrinth of the Spirits in Chinese and English: From Paratexts to Translation Strategies (Islas, 2026)
Introduction: This study analyzes the translation strategies employed in the Chinese and English versions of The Labyrinth of the Spirits by Carlos Ruiz Zafón. The novelty of the research lies in integrating the analysis of editorial paratexts with the examination of translation techniques applied to cultural elements. This approach makes it possible to assess how editorial and translational decisions jointly influence the reception of the work. The topic is particularly relevant as it highlights the interaction among the publishing market, the target culture, and translation strategies.Methods: A qualitative and comparative approach is adopted, based on Batchelor’s (2018) functional notion of paratext and Hurtado’s (2013) classification of translation techniques. The corpus consists of the English and Traditional Chinese editions of the novel. The analysis is carried out in two stages: first, the examination of covers, editorial information, and supplementary materials; second, a microtextual analysis of the translation of cultural elements using categories such as amplification, adaptation, generalization, and omission. The results are subsequently compared in order to identify strategic tendencies.Results: The analysis shows that the Chinese version combines amplification through notes and supplementary materials with cultural adaptations that facilitate comprehension, resulting, this way, in a form of disguised foreignization. The editorial paratexts reinforce this strategy by highlighting the foreign nature of the work through additional elements and greater translator visibility. In contrast, the English translation leans toward domestication through cultural adaptations, generalizations, and omissions that reduce cultural distance. Likewise, the English edition emphasizes the integration of the work into the local market through its paratextual resources.Conclusions: The results indicate that translation strategies are conditioned by both cultural factors and editorial decisions. The Chinese version tends toward disguised foreignization supported by paratextual amplification, whereas the English translation leans toward domestication to facilitate reception by target readers. Despite these differences, both versions aim to meet the expectations of their intended audience. The study confirms the importance of paratexts as an essential component in shaping translation strategies and highlights the need to analyze literary translation as an integrated phenomenon that combines text, context, and cultural mediation.
Keywords: The Labyrinth of the Spirits; Paratexts; Translation Strategies; Translation Techniques; Chinese; English; Carlos Ruiz Zafón